Технічні особливості зведення та мастерингу в музичних композиціях різних жанрів - Завацький, М. В. (ХНУРЕ, 2025)
Mixing and mastering are essential stages in the creation of high-quality music productions, significantly influencing the final sound. However, the approaches and techniques applied vary greatly depending on the genre. Each musical style has unique demands in terms of frequency balance, dynamic range, spatial processing, and overall sonic character. This paper explores the key technical aspects of mixing and mastering across genres such as hip-hop, electronic music, rock and metal, and classical music, with special attention to contemporary trends and advanced processing methods.
Keywords: музична композиція; high-quality music productions